Socioemotional wealth and IPO underpricing of family firms - Leitterstorf, Max P.; Rau, Sabine B. (Strategic Management Journal, 2014)
Socioemotional wealth ( SEW ), i.e., the noneconomic utility a family derives from its ownership position in a firm, is the primary reference point for family firms. Family firms are willing to sacrifice economic gains in order to preserve their noneconomic utility. Thus, we argue that family firms sacrifice IPO proceeds by choosing higher IPO underpricing than nonfamily firms if underpricing helps them protect their SEW . Our empirical results, based on a sample of 153 G erman IPO s, support our hypothesis. On average, family firms have 10 percentage points more IPO underpricing than nonfamily firms. Copyright © 2014 John Wiley & Sons, Ltd.